Dismantling the Commons: The Dispute Between Artisanal Fishermen and Hacendados in Chile (Boca de Rapel, 1769-1877) [Desmontando el Común: La Disputa Entre Pescadores Artesanales y Hacendados en Chile (Boca de Rapel, 1769-1877)] - Lacoste, P (Universidad de Murcia, 2018)
This article examines the struggle for control of coastal lands that took place between the artisanal fishermen of the mouth of the Rapel River and the landowners of Bucalemu hacienda, during the transition from the colonial period and the construction of the Chilean state after independence. It also examines the subsequent extension of state control over this territory within the framework of the transition to capitalism. The large-scale landowners or hacendados tried to expel the fishermen and their plebeian culture by various means: burning down their houses, depriving them of their work instruments, shackling them in private jails and putting theme in stocks. Yet the fishermen responded by defending their moral economy peacefully and only employed judicial means. Using original and unpublished documents from the National Archive of Santiago, this article also examines the role of the various actors in the conflict: fishermen, hacendados, judges and institutions. Both the justice system and the Parliament are found to have served the interests of the great haciendas or largescale landowners, in detriment of artisanal fishermen s rights. © 2018 SEHA.